2010
DOI: 10.1111/j.1525-1470.2010.01128.x
|View full text |Cite
|
Sign up to set email alerts
|

Patch Tests in Children: A Review of 13 Years of Experience in Comparison with Previous Data

Abstract: The true prevalence of allergic contact dermatitis (ACD) in children remains unknown. Our aim was to compare the results of patch tests in children with suspected ACD between two different periods of time and identify possible changes in emerging allergens. We compared contact allergens, gender, age distribution, and personal history of atopic dermatitis (AD), in correlation with the positivity of patch tests, between two equal periods of time (232 children tested during 1980-1993, period A, and 255 children d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
38
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 28 publications
(51 reference statements)
7
38
1
2
Order By: Relevance
“…4,12,13 É ainda controverso se os doentes com atopia têm maior ou menor propensão para DCA. 15,17 Neste estudo, a positividade dos testes epicutâneos é maior nos doentes com atopia pessoal (55,4%) o que pode sugerir que estes doentes podem ter um risco aumentado de desenvolver DCA ou maior exposição a medicamentos tópicos e emolientes, sobretudo no caso do eczema atópico.…”
Section: Discussionunclassified
“…4,12,13 É ainda controverso se os doentes com atopia têm maior ou menor propensão para DCA. 15,17 Neste estudo, a positividade dos testes epicutâneos é maior nos doentes com atopia pessoal (55,4%) o que pode sugerir que estes doentes podem ter um risco aumentado de desenvolver DCA ou maior exposição a medicamentos tópicos e emolientes, sobretudo no caso do eczema atópico.…”
Section: Discussionunclassified
“…Some authors have indicated that ACD is less prevalent in patients with AD (Uhr, 1960;Rystedt, 1985;De Groot, 1990;Katsarou et al, 1996;Stables et al, 1996;Brasch & Geier, 1997). Several authors were unable to detect differences between atopic and nonatopic subjects in this regard (Marghescu, 1985;Pambor et al, 1991;Goossens et al, 1995;Akhavan & Cohen, 2003;Beattie et al, 2007;Milingou et al, 2010). Against this others have even found a greater prevalence of ACD in patients with AD (De la Cuadra et al, 1990;Lammintausta et al, 1992;Dotterund & Falk, 1995;Lugovic & Lipozencic, 1997;Giordano-Labadie et al, 1999;Clayton et al, 2006).…”
Section: Contact Sensitisation and Atopic Dermatitismentioning
confidence: 96%
“…The widespread use as a preservative in a variety of compounds, including vaccine and antitoxin preparations, ophthalmic drops and contact lens solutions, www.intechopen.com may explain the high rate of positive patch test reactions (Katsarou et al, 1996;Militello et al, 2006;Goossens & Morren, 2006;Milingou et al, 2010). Low clinical relevance along with sensitization rates is probably related to its presence in vaccines (Novák et al, 1986;Osawa et al, 1991;Lee et al, 2009).…”
Section: Thiomersal and Metallic Mercurymentioning
confidence: 99%
See 1 more Smart Citation
“…Symptomatic children frequently exhibit positive patch testing to fragrances, as elucidated by several recent studies (Clayton et al, 2006;Hogeling & Pratt, 2008;Milingou et al, 2010;Zug et al, 2010). A particularly important diagnostic tool is the 'Fragrance Mix' patch test, which contains three cinnamic derivatives, two eugenol derivatives, geraniol, hydroxycitronellal and oak moss absolute extract.…”
Section: Skin Care Products and Fragrancesmentioning
confidence: 99%